Validation of the FAMACHA© method for selective anthelmintic treatment in dairy goat herds - Zárate Rendón, Daniel (2017)
A study in goats was carried out in the central coast of Peru to validate the FAMACHA© method for selective anthelmintic treatment in dairy goat herds. Blood and fecal samples were taken from 120 adult goats in five dairy goat farms. The micro haematocrit and the McMaster techniques plus faecal culture were used to evaluate the haematocrit, faecal nematode egg count (EPG) and to identify major nematode species, respectively. Spearman correlation coefficients were obtained. Two FAMACHA© criteria were used to identify animals that require anthelmintic treatment: 1: score 3, 4 or 5; 2: score 4 or 5, with <20% haematocrit in both cases. Sensitivity, specificity, positive predictive value and negative predictive value were assessed. Bunostomum sp and Haemonchus contortus were identified. Correlations between FAMACHA score, haematocrit and EPG were highly significant (p<0.001). False negatives were not found and the false positive rate was 67.5 and 46.7% for criteria 1 and 2 respectively. The true positive percentage was of 23.3% for both criteria, but the true negatives increased from 9.1 to 30%. The sensitivity of FAMACHA was 100% and the specificity was 12% for criterion 1 and 39.2% for criterion 2. The predictive positive value was 25.7 and 33.3% for criteria 1 and 2 respectively, while the negative predictive value was 100% for both criteria.